Leaf Characteristics and Yield Performance of Mungbean (Vigna radiata L.) Varieties under Different Levels of Shading (The Agriculturists, 2018)
An experiment was carried out to evaluate the leaf characteristics and yield performances of mungbean (Vigna radiata L.) under different light levels at the Crop Physiology and Ecology Research Field of Hajee Mohammad Danesh Science and Technology University, Dinajpur during March to June 2016. The experiment was laid out in a split plot design with three replications. Three light levels (L100 - 100 % light intensity, L75- 75 % light intensity and L50- 50% light intensity) were assigned in the main plots and four varieties (BARl Mung-6, BINA Mung-8, BINA Mung-5 and BU Mug-4) were assigned in subplots. Mosquito nets of different pore size were used for maintaining 75 and 50 percent light intensity. Leaf area was increased due to reduced light levels in all mugbean varieties but the increment was significant in BINA Mung-5 and BINA Mung-8 only at 75% light intensity at 40 days after sowing and only in BARI Mung-6 with L50 and BU Mug-4 with L75 and L50at 50 days after sowing. Due to reduced light levels, leaf dry weight was affected more in BINA Mung-5 and BU Mug- 4 than BARI Mung-6 and BINA Mung-8. Leaf thickness was reduced under shade in all the mungbean varieties, except in BU Mug-4 at 75% light intensity, and the reduction in leaf thickness was mainly due to the reduction in thickness of spongy layer. The palisade layer thickness was influenced insignificantly but spongy layer thickness was increased in BINA Mung-5 at 100% light intensity. The grain yields (t ha-1) of BARI Mung-6 and BINA Mung-8 remained stable under partial shade condition but the grain yield of BINA Mung-5 and BU Mug-4 was reduced drastically under partial shade condition. Higher leaf dry weight, number of pods plant-1, seeds pod-1, and heavier grains in BARI Mung-6 and BINA Mung-8 contributed to the higher grain yield plant-1 under partial shade condition than in BINA Mung-5 and BU Mug-4.The Agriculturists 2017; 15(2) 40-51